Identification of Animal Meat as Halal Product Authentication Using the Box Counting Method - Arum Andary Ratri; Ruth Ema Febrita; Indira Nuansa Ratri; I Wayan Suardinata (Politeknik Negeri Malang, 2023)
Awareness and the need for authentication or assurance of the authenticity of halal foods is a challenge in many countries, especially in Muslim countries. So, many countries where the majority of the population is Muslim are quite strict in ensuring the sale and purchase of meat, especially in traditional markets. Therefore, this study aim is to find a system to identify the types of meat from the image, such as the initiation of the manufacture of practical technology for the authentication of halal products. In this study, the box-counting method was used to determine the fractal dimension value of the identified animal flesh image. The container counting method uses the texture of the animal’s meat that has unique characteristics of each type. The results of the identification of the animal meat obtained were 24 tests which were correctly identified from a total of 36 test data. This translates into a 66,67% success rate for the system.